Paradoxical Embolism in a Patient with Patent Foramen Ovale; a Case Report - Khani, Mohammad; Bayat, Fariba; Rohani, Atoosheh; Pishgahi, Mehdi (Archives of Academic Emergency Medicine, 2018)
Patent foramen ovale (PFO) is usually asymptomatic; however, it could be quite dangerous for patients with right side clot in which thrombus can transmit the PFO and paradoxically emboli to systemic circulation. Here we present a patient with ankle fracture and paradoxical embolus to the brain, who was successfully treated with emergent thrombectomy, inferior vena cava (IVC) filter placement and anticoagulation therapy. Despite the high rate of mortality in these patients, fortunately our patient survived with surgical treatment.